2018
DOI: 10.1136/heartjnl-2018-313182
|View full text |Cite
|
Sign up to set email alerts
|

Potential spironolactone effects on collagen metabolism biomarkers in patients with uncontrolled blood pressure

Abstract: Treatment with spironolactone was associated with a reduction in serum biomarkers of collagen synthesis independently of blood pressure in patients with hypertension, suggesting that spironolactone might exert favourable effects on myocardial collagen synthesis and fibrosis. Whether this effect might contribute to slowing the progression to heart failure is worth investigating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 33 publications
1
36
0
Order By: Relevance
“…14,32,33 Trials of patients with obesity and/or hypertension have more consistently shown reductions in both PIIINP and PICP, as well as improvement in Doppler indices of left ventricular diastolic dysfunction. [34][35][36] Overall, the trials suggest that MRAs lead to more consistent reductions in serum PIIINP than PICP, markers of synthesis, with little effect on CITP, a marker of collagen degradation ( Table 1). 14,[27][28][29][30][32][33][34][35][36][37][38][39][40] The above observations provide the rationale for the Heart OMics in AGing (HOMAGE) trial, investigating whether spironolactone favourably alters markers of extra-cellular matrix remodelling for patients at increased risk of developing HF.…”
Section: Effect Of Spironolactone On Serum Markers Of Collagen Metabomentioning
confidence: 97%
See 1 more Smart Citation
“…14,32,33 Trials of patients with obesity and/or hypertension have more consistently shown reductions in both PIIINP and PICP, as well as improvement in Doppler indices of left ventricular diastolic dysfunction. [34][35][36] Overall, the trials suggest that MRAs lead to more consistent reductions in serum PIIINP than PICP, markers of synthesis, with little effect on CITP, a marker of collagen degradation ( Table 1). 14,[27][28][29][30][32][33][34][35][36][37][38][39][40] The above observations provide the rationale for the Heart OMics in AGing (HOMAGE) trial, investigating whether spironolactone favourably alters markers of extra-cellular matrix remodelling for patients at increased risk of developing HF.…”
Section: Effect Of Spironolactone On Serum Markers Of Collagen Metabomentioning
confidence: 97%
“…Median LVEF was normal at 63% (IQR 58-67%) and median plasma concentrations of NT-proBNP were 214 (IQR 137-356) ng/L ( Table 5). 36,[38][39][40][44][45][46][47][48][49][50] Left atrial volume and the ratio of E/E ′ were increased and left ventricular mass was at the upper limit of normal. On a symptom questionnaire (Appendix), the median score in response to the question 'Do you get breathless on moderate exertion (e.g.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…Previous reports showed that MRA treatment was associated with a decrease in collagen biomarkers, PIIINP in particular 4,10,14 . Hence, a decrease in PIIINP was used as a surrogate of anti-fibrotic response in the present study.…”
Section: Discussionmentioning
confidence: 91%
“…A cross-sectional study demonstrated that plasma PICP levels in HCM patients were positively correlated with myocardial PICP content and the histological myocardial collagen volume fraction [10]. Similarly, Ferreira et al also confirmed that the serum levels of PICP were significantly higher in patients with hypertension before drug treatment [11]. In contrast, in heart failure rats, Adamcova et al observed that collagen content in the left ventricle was increased, whereas plasma PICP levels were reduced by 42% as compared to the control group [12].…”
Section: Introductionmentioning
confidence: 85%